Conservation of Nutrients and Irrigation Potential of Domestic Waste Waters (Sewage Waters) Sans Pollution - Chhabra, R. (Journal of Soil and Water Conservation, 2022)
Sewage water contains large quantities of plant nutrients. A survey of major towns of Haryana has shown that these waters, in addition to meeting the water requirement, add about 36.2, 5.7, 54.0 and 15.6 kg. of N, P, K and S, respectively in one application when used for irrigation. However, considering the social attitude, odour, hazards due to pathogens, soluble organic compounds; toxic elements (Pb, Cd & Ni) and their large volumes near the cities, only 10 to 50 per cent of these waters are being utilised while the rest are causing serious river and land pollution.A system of forestry has been developed at CSSRI. Using eucalyptus, leucaena andpoplar forest species to utilise the nutrients of these waters for fuel wood and timber production. In the proposed system, one hectare of eucalyptus plantation can give a gross return of Rs. 9691, 22723, 46880 and 69780 in the first, second, third and fourth year, respectively. This will be in addition to the costs saved on pretreatment of sewage and control of mosquitoes and other pathogenic.